PSXI-19 Evaluation of Salmonella Enteritidis (S.E.) Cecal Excretion and Ovary Infection Rates After SE Challenge in Commercial Layer Pullets fed with Feed Energy Company Product R2. (21st September 2022) - Mahfuz, Abdullah; Jones, Mathew; Dasari, Mohan; Berghaus, Roy; Hofacre, Charles L
Abstract: Salmonella enteritidis is one of the leading bacterial causative agents of acute human gastroenteritis from poultry. The objective of this study was to determine the efficacy of the patent pending low pKa, lipid-based natural R2 product of Feed Energy on commercial layer pullets using a Salmonella enteritidis challenge model. One-day-old HyLine W-36 layer pullets were placed in two separate rooms (116 sq.ft.) at 48 birds per pen. At 10 weeks of age, pullets were placed in individual cages of an A-Frame layer cage with a plastic wall between the R2 treatments (48 cages) and 48 cages for the challenge control. All birds were orally gavaged S.E. at 17 weeks with 5.2x108 CFU/bird. The dietary treatments from day 1: Control: Basal Diet + Distiller corn Oil (DCO), Treatment: Basal Diet + R2 product. The birds were fed a starter feed from day 1 to 12 weeks of age with 2.5% added fat and grower diet from 12 to 20 weeks with 1% added fat. Salmonella prevalences in ceca, ovaries, and cloacal swabs were compared between treatments and weeks using logistic regression. Salmonella CFUs in culture-positive samples were compared using linear regression. All statistical testing assumed a two-sided alternative hypothesis, and P < 0.05 was considered significant. Ceca and ovary samples were evaluated from one-half of the birds at 1 week and 3 weeks post challenge. At both sample times, the birds fed the R2 product had numerically less S.E. prevalence in ceca, ovaries, and cloacal swabs. Although there was not a statistical difference for each individual tissue tested, there was an obvious trend in reduction over time that would indicate the R2 product may be helping hens to more rapidly clear S.E. colonization and long-term benefits in preventing and/or reducing S.E. colonization of the ceca and ovaries.